2008
DOI: 10.1016/j.pnpbp.2007.09.016
|View full text |Cite
|
Sign up to set email alerts
|

MRI study of the cerebellum in young bipolar patients

Abstract: Prior studies demonstrate structural abnormalities of cerebellar vermis in adult bipolar patients. Cerebella of 16 young bipolar patients (mean age ± S.D. = 15.5 ± 3.4) and 21 healthy controls (mean age ± S.D. = 16.9 ± 3.8) were examined using magnetic resonance imaging. The volumes of right, left and total cerebellum, vermis, and areas of vermal regions V1 (lobules I-V), V2 (lobules VI-VII), and V3 (lobules VIII-X) were measured. Analysis of covariance, with age, gender, and intra-cranial brain volume as cova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 25 publications
4
39
1
3
Order By: Relevance
“…It is also thought that it might have a role in the regulation of sensory, procedural, linguistic, and emotional activities via its connections with limbic and cortical association areas. Therefore, it is suggested that cerebellum plays an important role on the regulation of mood, and cerebellum anomalies might contribute to the pathophysiology of mood disorders (21,22,23). For example, Schmahmann described "cerebellar cognitive affective syndrome, " which includes impairments in executive functions, visuospatial, and linguistic abilities, along with a large spectrum of affective symptoms ranging from depression and affective blunting to disinhibition and psychotic symptoms, in patients having cerebellar lesions (24).…”
Section: Discussionmentioning
confidence: 99%
“…It is also thought that it might have a role in the regulation of sensory, procedural, linguistic, and emotional activities via its connections with limbic and cortical association areas. Therefore, it is suggested that cerebellum plays an important role on the regulation of mood, and cerebellum anomalies might contribute to the pathophysiology of mood disorders (21,22,23). For example, Schmahmann described "cerebellar cognitive affective syndrome, " which includes impairments in executive functions, visuospatial, and linguistic abilities, along with a large spectrum of affective symptoms ranging from depression and affective blunting to disinhibition and psychotic symptoms, in patients having cerebellar lesions (24).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos em geral demonstraram redução do volume do vér-mis cerebelar 28 ; porém, em relação ao volume dos hemisférios cerebelares, os resultados são controversos 28,29 . Nesse sentido, pesquisa realizada pelo nosso grupo que mediu o tamanho das diversas áreas do cerebelo em pacientes bipolares tipo I eutí-micos mostrou perda volumétrica tanto do vérmis quanto dos hemisférios cerebelares 30 .…”
Section: Cerebelounclassified
“…It plays a central role in neural circuitries related to superior cognitive functions, which are usually disrupted in BD patients [10,11,12]. Interestingly, it has also been suggested that in BD, cerebellar shrinkage correlates with the number of affective episodes [13,14,15] as well as with long duration of illness and age [16,17]. Of the structures forming the cerebellum, the vermis and its subareas (the superior vermis, superior posterior vermis, and inferior posterior vermis), in particular, seem to play a key role in the pathophysiology of BD [14], especially with regard to behavioral and executive alterations [8,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has also been suggested that in BD, cerebellar shrinkage correlates with the number of affective episodes [13,14,15] as well as with long duration of illness and age [16,17]. Of the structures forming the cerebellum, the vermis and its subareas (the superior vermis, superior posterior vermis, and inferior posterior vermis), in particular, seem to play a key role in the pathophysiology of BD [14], especially with regard to behavioral and executive alterations [8,18,19,20]. Indeed, from magnetic resonance imaging (MRI) studies, there are reports of a significant alteration of the volume of the vermis and its subareas in BD patients when compared to healthy controls, supporting the notion of cognitive cerebellar deficit in BD [13,14,16,17,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation